Dilemma of accounting online learning system in the covid-19 pandemic in indonesia: a complex-phenomenology approach - Muhammad Ikbal; Yana Ulfah; Irwansyah Irwansyah; Karmila Aulia Sahaja; Alsyadilla Anggita (Inovasi : Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
We are working on a research design that explores the experiences of Accounting Lecturers throughout Indonesia, how they experience learning online in the field of Accounting. Accounting has its characteristics in the learning process. Accounting is a combination of deepening thinking intelligence, use of mathematical logic, and expertise in preparing financial reports. We use a Qualitative paradigm with a Complex Phenomenology approach, combining in-depth interviews to gather information on several informants while distributing survey questionnaires. The results show various problems that arise in online learning. We have examined high-stress levels separately what triggers stress and what are the factors that can relieve stress. The contribution of this work is certainly useful for universities to design accounting learning systems to reduce various weaknesses and problems that arise.